Smart city development strategies: data determinism and tehnological sovereignty - Dimitrijevic, Lazar (Sociološki pregled, 2023)
This paper analyzes the role of the citizen through the nexus between the notion of ‘the right to the city’ and the current challenges of data integrity. The introductory discussion explains the contingencies of data, regarding the citizen, and the postulations of technological sovereignty as an alternative to the corporate smart city design. The deployed method includes content analysis and literature reviews pertaining to the phenomenon of data alienation, data security, and the political dichotomies between the “hard” and “soft” approaches to the strategies of smart city development. The first part elucidates the position of data in the smart city construct, whilst the second part inquires about the social and political role of the citizen in smart cities.
Keywords: smart city development; data determinism; technological sovereignty; citizenship; personal data